Prevalence and Factors Influencing Substance Use among Ethnically Diverse Adolescents in the Upper Northern of Thailand - Chaichana, Thirawat; Srichan, Peeradone; Wongnuch, Pilasinee (Disease Control Journal, 2026)
In contemporary society, characterized by cultural diversity and varying living environments, adolescents face heightened risks of substance use. This cross-sectional analytical study aimed to investigate the prevalence and factors influencing substance use. Participants included 238 adolescents (aged 15-17 years) recruited via simple random sampling. Research data were gathered through questionnaires between December 2024 and February 2025. Data was analyzed using descriptive statistics and logistic regression analysis. The findings revealed that alcohol consumption was the most prevalent form of substance use among adolescents (56.3%), followed by kratom use (18.5%), tobacco product use (13.9%), and cannabis use (7.1%). Tobacco use was significantly associated with being male (AOR=5.8; 95% CI: 2.39-14.39), alcohol consumption (AOR=33.1; 95% CI: 3.06-192.84), and kratom use (AOR=3.1; 95% CI: 1.40-8.58). Alcohol consumption was associated with depression (AOR=2.3; 95% CI: 1.25-4.34) family and peer factors (AOR=0.4; 95% CI: 0.23-0.89) tobacco use (AOR=22.2; 95% CI: 2.80-176.16) and kratom use (AOR=17.2; 95% CI: 3.83-77.31). Cannabis use was associated with being male (AOR=46.6; 95% CI: 6.14-403.02) and kratom use (AOR=65.6; 95% CI: 9.54-452.43). Kratom use was associated with tobacco use (AOR=2.8; 95% CI: 1.09-7.50), alcohol consumption (AOR=14.4; 95% CI: 3.19-65.80), and cannabis use (AOR=25.5; 95% CI: 4.49-145.01). The findings reveal a rising trend in substance use prevalence, particularly polydrug use. It recommended that rigorous and sustained policies be established to control and prevent access to alcohol and kratom among the adolescent population.